Sucralose: From Sweet Success to Metabolic Controversies—Unraveling the Global Health Implications of a Pervasive Non-Caloric Artificial Sweetener - José Alfredo Aguayo-Guerrero; Lucía Angélica Méndez-García; Helena Solleiro-Villavicencio; Rebeca Viurcos-Sanabria; Galileo Escobedo (Life, 2024)
Sucralose is a food additive initially used to mitigate glycemic peaks and calorie intake in patients with diabetes and obesity. Although sucralose has been considered safe for human consumption, the World Health Organization (WHO) issued a global alert in 2023 concerning the potential health implications of this artificial sweetener. This review aims to comprehensively explore the effects of sucralose intake on human health by understanding sucralose absorption, metabolism, and excretion. We also outline the role of the sweet taste 1 receptor 3 (T1R3) in mediating sucralose-dependent signaling pathways that regulate satiety, incretin release, and insulin response. Finally, we discuss the impact of sucralose on microbiome dysbiosis, inflammatory response origin, liver damage, and toxicity. Gaining a deeper understanding of the manifold effects of sucralose on human physiology will help promote further studies to ensure its consumption is deemed safe for a broader population, including children, adolescents, and pregnant women.